The Esquire and the Pettifogger: Reintroducing James Cobbe and Rethinking his Alopichos - Menna, Michael Lind (Early Theatre, 2025)
This article reexamines an overlooked manuscript play titled Alopichos and dated 1623. Composed by ‘Iames Cobbe Esquior’ while studying law at Gray’s Inn, the document warrants interdisciplinary reconsideration as a remnant of England’s changing legal and playing professions, in light of its ambiguous status as a piece of amateur law-school drama or aspirational entry to the commercial theatre. In staging the exploits of an ‘old crafti pettyfogger’ named Versuto, Alopichos offers an occupational spin on city comedy befitting an Inns of Court audience. That story, however, does not explain why the manuscript play advertises a performance at the Globe.